Analisis Pengaruh Rasio Pembiayaan (Financing To Deposit Ratio) Dan Rasio Perputaran Aktiva (Total Asset Turn Over) Terhadap Pembiayaan Bermasalah (Non Performing Financing) Pada Bank Syariah Indonesia Periode 2016-2020 - Siswoyo, Slamet Tedy; Japlani, Ardiansyah; Almutsiroh, Lutfi (Jurnal Manajemen DIVERSIFIKASI, 2023)
This study aims to determine how the influence of independent variables (FDR and TATO),either partially or simultaneously on the dependent variable (NPF) in Indonesian Islamic Banks.This research includes research using quantitative methods. the type of data used is secondarydata obtained through the official website of Bank Syariah Indonesia (BSI), namelywww.bankbsi.co.id. The data taken is seen from BSI's annual financial statements for the 2016-2020 period, from 15 BSI samples, namely Bank Syariah Mandiri, BRI Syariah, and BNISyariah. The data analysis method used is panel data regression analysis, with the Chow test,Lagrange multiplier test and hypothesis testing (R2test, F test, and T test), the panel dataregression estimation model used is the Common Effect Model, data processing using the Eprogram -View 9. The results of this study show that the FDR and TATO variablessimultaneously have no and significant effect on Non-performing Financing (NPF). The result ofthe coefficient of determination test (R2) is 40.62% while the remaining 59.38% is influenced byother factors outside the study. The results of the partial study of FDR have no effect and are significant on Non-performing Financing (NPF) with a t-count value of 0.389153 < t-table 2.179 and a significance value of 0.7040 which means > 0.05. and TATO has no and significant effect on Non-performing Financing (NPF) with a t-count value of 0.174297 < t-table 2.179 and a significance value of 0.6885 which means > 0.05.